Plasmon resonance spectroscopy: probing molecular interactions at surfaces and interfaces. Issue 3 (2001) - Salamon Salamon, Zdzislaw Zdzislaw; Tollin Tollin, Gordon Gordon
Abstract : Surface plasmon resonance (SPR) spectroscopy can be applied to a wide variety of interfacial systems. It involves resonant excitation by polarized light of electronic oscillations (plasmons) in a thin metal film. These generate a surface‒localized evanescent electromagnetic field that can be used to probe the optical properties perpendicular to the film plane of materials immobilized at the surface. Spectra depend on three parameters: refractive index ( n ), absorption coefficient ( k ) and thickness ( t ). Maxwell's equations provide an analytical relationship between these properties and SPR spectra, allowing their evaluation. An extension of this methodology, called coupled plasmon‒waveguide resonance (CPWR or PWR), is able to characterize film propertiesboth perpendicular and parallel to the surface plane. In a PWR device, the metal film is covered with a dielectric coating that acts as an optical amplifier, provides protection for the metal layer, and possesses a surface that allows various molecular immobilization strategies. The exceptionally narrow line widths of PWR spectra yield enhanced sensitivity and resolution. The application of this technology to several biomembrane systems will be described, demonstrating its ability to observe both binding and structural events occurring during membrane protein function.